An evolutionary algorithm for the capacitated arc routing problem - Vianna, Dalessandro Soares (2009)
The Capacitated Arc Routing Problem (CARP) consists of visiting a subset of edges of the graph that describes the problem. CARP applications include urban waste collection and inspection of power lines. The CARP is NP-hard, even in the single-vehicle case (called Rural Postman Problem). In this case, the use of metaheuristics is an efficient solution strategy. This paper proposes a hybrid genetic algorithm for the CARP, which is tested on available instances of the literature. The results obtained until now show the effectiveness of the proposed algorithm when it is compared with lower bounds described in the literature.